In vitro biomimetic models for respiratory diseases: progress in lung organoids and lung-on-a-chip - Xiaochun Zhang; Haolin Liu; Haofeng Cheng; Yuhui Cui; Junli Wang; Qianru Yao; Ping Wang; Yuan Hu; Yu Wang (Stem Cell Research & Therapy)
Abstract Respiratory diseases pose a growing global public health challenge due to their rising incidence and mortality. Conventional cellular and animal models fall short in replicating the complex three-dimensional (3D) microenvironments of the lung and are limited by species differences, restricting their clinical relevance. Emerging technologies, such as lung organoids (LOs) and lung-on-a-chip (LOC), combine stem cell differentiation, microfluidic systems, and biomechanical cues to create advanced in vitro models that address these limitations. LOs leverage the innate ability of human pluripotent stem cells (hPSCs) to self-organize, faithfully mimicking lung development, cellular diversity, and the native tissue environment. In comparison, LOC platforms employ flexible biomaterials to recreate the respiratory microenvironment dynamically, enabling a detailed study of normal physiology and disease states. This review highlights recent advancements in LOs- and LOC-based models across five key respiratory conditions: infections, chronic obstructive pulmonary disease (COPD), asthma, pulmonary fibrosis (PF), and lung cancer. Furthermore, it discusses their capacity to deepen understanding of disease mechanisms, accelerate drug discovery, enhance pharmacological evaluation, and serve as comprehensive tools for respiratory research.